Permainan Tradisional Boy-Boyan: Upaya Peningkatan Kemampuan Mengenal Angka dalam Bahasa Madura - A’yun, Qurrotu; Nurhayati, Nurhayati; Damayanti, Nadifa Alfani; Nadhifah, Ainun; Fadilah, Nur Utami; Nazarullail, Fikri (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Trunojoyo Madura, 2024)
The study aims to determine the development of number recognition skills in Madurese language for children aged 5-6 years and to assess the percentage improvement in number recognition skills in Madurese among Group B children at Tanjung Jati Kindergarten through the traditional game